How to identify and use the strengths of a non-verbal autistic child - Laurent Mottron, Claudine Jacques, YU Luodi (Xin yixue)
Persons with prototypical autism often present unique strengths that traditional intelligence assessments overlook， together with absence of oral language at the preschool age. Here， we propose a strengths-based approach in understanding and engaging with non-verbal autistic children. It emphasizes recognizing unique intellectual abilities often masked by communication challenges and conventional understanding of repetitive behaviors. By observing these children’s interests in structured objects， patterns， and screens， caregivers and clinicians can gain insights into their cognitive potential. We then present methods to leverage autistic strengths to support wellbeing of the families， including using “lateral tutorship” —a non-intrusive， side-by-side engagement method—as a way to connect with autistic children， respecting and utilizing their intrinsic learning style.